The Influence of Online Business on Consumer Purchasing in Yogya Grand Subang - Nida Hopia; Nunung Siti Maryam; Veny Robiatul Saiddah; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat (Journal on Education, 2023)
E-commerce helps busy people meet their demands. E-commerce marketplaces abound in Indonesia. Retailers like Yogya Grand Subang must give media for online shopping to compete. Yogya Grand Subang uses E-commerce to create Yogyaonline.co.id, an online shopping media. This study aims to determine the effect of online business on consumer purchasing power in retail stores, the elements of online buying and selling, the tendency of people to shop online or directly to the store, the online shopping media owned by Yogya Grand Subang, and the factors that encourage online buying and selling. The research method used is qualitative using primary data and secondary data. Primary data collection techniques with interviews and secondary data by reading, reviewing, and analyzing the results of the same research. The results of this study indicate that online business has an effect on increasing consumer purchasing power and has a significant effect on increasing sales at Yogya Grand Subang. Factors that encourage people to do e-commerce because it is more efficient, more complete, cheaper, more practical.